Protocol for a randomized controlled trial of steroid versus methotrexate as first-line monotherapy in the management of idiopathic granulomatous mastitis - Serene Si Ning Goh; Peter Cheung; Sen Hee Tay; Margaret Ma; Thomas Choudary Putti; Bee Choo Tai; Karen Kaye Casida; Zhi Hua Chua; Ying Jia Chew; Nur Khaliesah Binte Mohamed Riza; Jenny Liu; Mikael Hartman (PLoS ONE, 2025)
Background Idiopathic granulomatous mastitis (IGM) is a rare inflammatory breast disease affecting mainly young to middle aged women. Its aetiology is idiopathic and poorly understood, but recent evidence supports its autoimmunity pathogenesis. This pathogenesis supports the current first line treatment involving steroid monotherapy or steroid combination therapy with methotrexate, however, there is no single well-established treatment protocol that has been shown to most effectively cure the disease. Thus, this prospective, open, two arm randomised controlled trial comparing the effectiveness of steroid versus methotrexate therapy in the treatment of IGM patients was developed, with the hypothesis that methotrexate has a higher 6-months clinical complete response and radiologically complete response rate than steroid monotherapy. Methods This trial will be conducted at the Breast Care Center of the National University Hospital Singapore. To be eligible, patients must have undergone breast ultrasound, biopsy, and histologic diagnosis of IGM. Forty eligible patients between the ages 21–60 will be recruited obtaining informed consent. Baseline blood tests and imaging will be obtained during screening phase. Eligible patients after the screening phase will be randomised to either oral corticosteroid or methotrexate group. Treatment phase commences in which patients in both arms will receive either oral corticosteroid or oral methotrexate over 3 months, with follow-ups conducted at 6- and 12-months post randomisation. Safety measures including reporting of adverse events along the course of the trial will be observed. The primary outcome is 6-month complete clinical or radiological response rate, alongside time to cCR post randomization, treatment failure (TF) rate, and relapse rate (RR). Secondary outcomes include identification of drug adverse effect, frequency of surgical intervention, determination of potential biomarkers, and patient reported outcomes. Ethics and Dissemination This study is approved by the ethics committee of the National University Singapore (DSRB reference number 2023/00773). Results of this trial will be shared and presented in local and international scientific conferences, and will be published in international journals.